Spatial analysis for water supply in seismic emergencies: the Lima-Callao metropolitan area - Santa-Cruz, Sandra; Fernández de Córdova, Graciela; Vilela, Marta; Pajuelo, José; Santa-María, María; Muñoz, Kevin (Frontiers in Built Environment, 2024)
In urban areas exposed to high-magnitude earthquakes, the drinking water supply would be severely damaged, and domestic services would be disrupted for a large part of the population in the event of an earthquake. The Lima-Callao metropolitan area in Peru, South America, is expected to experience an 8.8 Mw earthquake, and it is estimated that approximately 90% of the population would not have immediate access to emergency water in the case of such an event. The main objective of this paper is to define criteria for a spatial analysis method to guide the design criteria for an Emergency Water Supply System (EWaSS). The EWaSS is an alternative for safe water supply in a post-disaster situation that would provide immediate and autonomous operation during the first 72 hours of the emergency. This paper combines territorial, urban resilience and participatory approaches and presents the results of an interdisciplinary research with social impact. Thus, it examines the urban territory at macro-, meso-and micro scales; physical-spatial variables indicating risk levels and possible public spaces to implement the system; and socio-spatial variables regarding the population, risk perception and participation in management to strengthen urban resilience. Normative tools and the Geographic Information System are used to spatialize and systematize quantitative and qualitative information. The results show the physical-spatial and social viability of urbanized areas and the system design criteria that guide local actors in making decisions at the three levels of emergency management.